Pest categorisation of Venturia nashicola. (24th November 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Gregoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; et al.
Abstract: The Panel on Plant Health performed a pest categorisation of Venturia nashicola, the causal agent of Asian pear scab, for the European Union (EU). The pathogen is a well‐defined, distinguishable fungal species affecting Pyrus pyrifolia var. culta, P. ussuriensis and P. bretschneideri in Asian countries. P. communis (European pear) is not a host of V. nashicola, but the host status of other Pyrus species is unclear. V. nashicola is not known to occur in the EU. It is listed in Annex IIAI of Directive 2000/29/EC. The pathogen could potentially enter the EU on host plants for planting and fruit originated in infested countries. There are no climatic factors limiting the potential establishment and spread of the pathogen in the EU, as its epidemiology is similar to those of Venturia inaequalis (apple scab) and Venturia pyrina (European pear scab), which are well‐established in the EU. The hosts are present in the EU, but no data were found on their abundance and distribution. In the infested areas, V. nashicola causes premature leaf and fruit drop and fruit distortion resulting in considerable yield/quality losses. The introduction of the pathogen into the EU could cause yield/quality losses and environmental consequences because of the additional fungicide sprays for disease control. Cultural practices and chemical measures applied in the infested areas reduce the inoculum sources but they cannot eliminate the pathogen. Phytosanitary measures are available to mitigate the risk of introduction and spread of the pathogen in the EU. All criteria assessed by EFSA for consideration as a potential Union quarantine pest are met. As V. nashicola is not known to occur in the EU, this criterion assessed by EFSA to consider it as a Union regulated non‐quarantine pest is not met.